2011
DOI: 10.1111/j.1365-2206.2011.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to collaboration on behalf of children with challenging behaviours: a large qualitative study of five constituent groups

Abstract: Inter‐agency collaboration is seen as an effective way to support children and families with multiple and complex needs. Children in out‐of‐home care, especially those exhibiting challenging and disruptive behaviour, often require the services of multiple agencies. Ninety‐two South Australian stakeholders experienced in supporting children in out‐of‐home care were interviewed about their experience of collaborative practice, using the specific example of supporting children with extremely challenging behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 26 publications
1
32
0
2
Order By: Relevance
“…Consistent with the existing literature (McLean, 2012;Yang et al, 2013;Ziviani et al, 2013), effective service coordination was often hindered by stakeholder turnover which created instability between interagency relationships, and a lack of collaborative infrastructure. High turnover within the partnering agencies results not only in disrupting service delivery to clients, but also destabilizes relationships across stakeholder groups, which compromises interagency collaboration (Acri et al, 2014;McLean, 2012;Mitchell, 2014;Yang et al, 2013;Ziviani et al, 2013).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Consistent with the existing literature (McLean, 2012;Yang et al, 2013;Ziviani et al, 2013), effective service coordination was often hindered by stakeholder turnover which created instability between interagency relationships, and a lack of collaborative infrastructure. High turnover within the partnering agencies results not only in disrupting service delivery to clients, but also destabilizes relationships across stakeholder groups, which compromises interagency collaboration (Acri et al, 2014;McLean, 2012;Mitchell, 2014;Yang et al, 2013;Ziviani et al, 2013).…”
Section: Discussionsupporting
confidence: 63%
“…High turnover within the partnering agencies results not only in disrupting service delivery to clients, but also destabilizes relationships across stakeholder groups, which compromises interagency collaboration (Acri et al, 2014;McLean, 2012;Mitchell, 2014;Yang et al, 2013;Ziviani et al, 2013). High turnover results in a continuous influx of young, less experienced child welfare workers who are respondents perceived to be less prepared for helping link young children on their caseloads to high quality ECE programs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The intake procedure of the mental health services hindered the initial decision of the juvenile judge to refer a minor with mental disorders to a mental health service, while the other two barriers hindered the decision to prolong the minor's period of admission at the mental health service. Each of these barriers has been mentioned in previous research on the collaboration between the juvenile court and mental health services (Darlington, Feeney, & Rixon, 2004, 2005McLean, 2012). The fact that the barriers information exchange and power conflict, were mentioned, especially by the juvenile judges and the social services investigators, revealed these actors' perspective on the role of the youth psychiatrist and their own role in the decision-making process.…”
Section: The Role Of the Youth Psychiatristmentioning
confidence: 89%
“…Specifically, the worker provides services and supports to foster parents (Blakey et al 2012), and the quality of support provided by the worker to the foster parent is of central improtance (Vanschoonlandt et al 2014). Workers keep foster parents up to date with policy and system changes as they occur (Galehouse et al 2010) and joint problem solve as well as help with direct intervention for foster children who are struggling (McLean 2012). Use of technology is also an important need in the relationship (e.g.…”
Section: Introductionmentioning
confidence: 98%